Upaya Pusat Kegiatan Belajar Masyarakat Satria Tama Purwokerto Dalam Menanamkan Jiwa Kewirausahaan Bagi Siswa - Dziky Fauzy; Nur Isnaeni Widiastuti; Annaafi Putra Ramadhan; Iqvan Maulana; Kholifah Nur Romadoni; Galih Safangaturohman; Layla Mardliyah (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
Abstract PKBM Satria Tama Purwokerto was established on February 14, 2006, as an equivalency education institution focused on community empowerment and reducing school dropout rates. The institution provides Package A, B, and C programs using modules from the Ministry of Education, and involves 92 students and 8 tutors. In addition to academic learning, PKBM also provides skills training such as fish farming and urban agriculture to improve students' practical competencies and environmental awareness. The Merdeka Curriculum, with the theme P5